(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The provisions of general terms of sale and delivery of 1982 were adjusted to the rules of the ,economic reform and laws from the years 1981—.1982 connected with it. They correspond with the principle of self-dependence of socialized economic subjects and freedom of contract. The limitation of these principles is, however, necessary and is manifested mainly in keeping and obligation to conclude a contract. In the actual state of law the obligation may result from the law (sale of spare parts, delivery of fiat money and securites, obligatory brokerage, distribution, limited deliveries of fuels and energy) or from the decision of the competent organ (founder’s organ in relation to the enterprise, administrative organ in relation to a co-operative). General terms of sale and delivery also comprise contracts on material and technical procurement, contracts concluded as a result of government orders and co-operating contracts. The provisions of general terms of sale and delivery have, as a rule, discretionary character expect for provisions on official and regulated prices, warranty for defects, penalty for breach of a contract. A conclusion, change, dissolution; withdrawal from a contract were regulated — with minor modifications — similarly to the general terms of sale and delivery of 1973. The same refers to the fulfilment of a contract, however, new provisions on transport insurance, prices and settlements have been taken into consideration. The provisions on warranty for defects were based on similar principles, with some modifications. The provisions on ’the general terms of sale and delivery distinguish at present legal guarantee and contractual guarantee; the former comprises only goods enumerated in new lists of 1983. Commpensation responsibility is based on art. 471-474 of the civil code because general terms of sale and delivery .do not separately regulate the grounds for responsibility of a debtor. The principle was confirmed by the resolution of arbitrage of 1984. Special grounds provided for by general terms of sale and delivery refer to the responsibility of a seller for consequences of decision of a supervisory organ and activities of third persons. Penalty for the breach of a contract is, similarly as in the civil code, contractual reservation. The parties may freely define its elements. Strict regime concerns only penalties for defects of goods; they are binding ex lege. The provisions on export and import sale were not considerably changed. A new solution introduced in the amendment of 1983 is a ’contract on delivery of fiat money